Stable Isotope Palaeodietary and Radiocarbon Evidence from the Early Neolithic Site of Zemunica, Dalmatia, Croatia. (10th April 2017) - Guiry, Eric; Karavanić, Ivor; Klindžić, Rajna Šošić; Talamo, Sahra; Radović, Siniša; Richards, Michael P.
Abstract : The Adriatic Sea and Balkan Peninsula were an important corridor for the spread of agriculture northwards and westwards from the Near East into Europe. Therefore, the pace and nature of the Mesolithic-Neolithic transition along the Adriatic coastline has important implications for the movement of new peoples and/or ideas during one of the most eventful periods in European prehistory. We present new Early Neolithic radiocarbon and stable isotope evidence from humans and animals from the Zemunica cave site in Dalmatia, Croatia. The results show that these humans date to the earliest Neolithic in the region, and they have completely terrestrial diets, where the main protein source was most likely to have come from domesticated animals. Data are then compared to previous isotope and archaeological evidence to explore models for the spread of agriculture along the eastern Adriatic coast. Abstract : La mer Adriatique et la péninsule des Balkans jouèrent un rôle de taille dans la dissémination de l'agriculture vers le nord et l'ouest de l'Europe à partir du Proche Orient. Le caractère et la rapidité de la transition entre le Mésolithique et le Néolithique le long de la côte adriatique a donc eu des conséquences importantes pour le mouvement de nouveaux arrivants et/ou d'idées pendant la phase la plus mouvementée de la préhistoire européenne. Nous présentons ici une série de nouvelles datations radiocarbone et une analyse des isotopes stables sur la base d'ossements humains at animaux provenant de la grotte de Zemunica en Dalmatie (Croatie). Les résultats indiquent que les occupants de Zemunica appartenaient à la phase la plus ancienne du Néolithique de cette région et que leur régime alimentaire était entièrement terrestre, la source principale de protéines provenant vraisemblablement d'animaux domestiques. Enfin, en comparant les résultats obtenus à des données archéologiques et isotopiques plus anciennes, nous examinons certains modèles concernant la propagation de l'agriculture le long de la côte adriatique orientale. Translation by Madeleine Hummler Abstract : Die Adria und die Balkanhalbinsel waren bedeutende Verbindungswege für die nördliche und westliche Ausbreitung der Landwirtschaft aus dem Nahen Osten nach Europa. Die Geschwindigkeit und die Art des Übergangs vom Mesolithikum zum Neolithikum entlang der adriatischen Küste hatten erhebliche Auswirkungen auf den Verkehr von neuen Bevölkerungen und/oder Ideen in einer der ereignisreichsten Epochen der europäischen Urgeschichte. In diesem Artikel werden neue Radiokarbon Datierungen und die Ergebnisse von isotopischen Analysen von Menschen und Tiere aus der frühneolithischen Höhle von Zemunica in Dalmatien (Kroatien) vorgelegt. Es ergibt sich, dass man diese Menschen in die älteste neolithische Phase des Gebietes datieren muss und dass ihre Ernährung völlig ländlich war. Haustiere waren sehr wahrscheinlich die Hauptquelle von Proteinen. Diese Angaben werden dann mit früher erhaltenen isotopischen und archäologischen Daten verglichen um Modelle, welche die Ausbreitung der Landwirtschaft entlang der ostadriatischen Küste betreffen, zu erwägen. Translation by Madeleine Hummler